Cyanobacteria and algae from Chýnov and Koněprusy caves (Czech Republic) - Wipplingerová, Michaela; Pokorný, Jan; Kaštovský, Jan (International journal of speleology, 2025)
Algae and cyanobacteria have been studied in two so far phycologically unexplored show caves (Chýnov and Koněprusy) in the Czech Republic. Taxa were identified morphologically using cultivation and subsequent light microscopy, while problematic cyanobacterial species were verified by sequencing the genes for 16S rRNA and 16S–23S internal transcribed spacer. A total of 13 cyanobacterial taxa were found, two Bacillariophyceae, three Xanthophyceae, four Chlorophyceae, six Trebouxiophyceae, 11 Streptophyta, and three Euglenida; many of these species were found for the first time in the caves. The darker parts of the caves were dominated by cyanobacteria, and green algae were found predominantly right next to light sources. This community associated with artificial light sources is referred to as “lampenflora” and is often a detrimental factor to speleothems and cave paintings.